2024
DOI: 10.4236/gep.2024.121007
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Saltwater Intrusion in Coastal Regions of Lagos, Nigeria

Obunadike Callistus,
Akerele D. Daniel,
Abiodun O. Pelumi
et al.

Abstract: This paper explains various factors that contribute to saltwater intrusion, including overexploitation of freshwater resources and climate change as well as the different techniques essential for effective saltwater intrusion management. The impact of saltwater intrusion along coastal regions and its impact on the environment, hydrogeology and groundwater contamination. It suggests potential solutions to mitigate the impact of saltwater intrusion, including effective water management and techniques for managin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In Nigeria, this challenge has affected over 1000 km of the coastline of Nigeria extending from Rivers and passes through Bayelsa, Akwa Ibom, Cross Rivers State, Delta, Ondo, Ogun and Lagos States, all of which share their southern border with the Atlantic Ocean and has been reported in several literatures. [Adeyemo et al, 2017[16]; Ohwoghere-Asuma, and Oghenevovwero 2017 [17]; Oloruntola et al, 2019[18]; Yusuf et al, 2021[19]; Atuluchukwu et al, 2022 [20]; A ah et al, 2018 [21]; Edet 2017 [22], Akerele et al, 2023[23], Inim et al, 2020 [24], Obunadike et al, 2024 [25]]. The works of Oteri and Atolagbe (2003) [26] reported that salt water incursion has been occurring especially in coastal areas of the Niger Delta, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, this challenge has affected over 1000 km of the coastline of Nigeria extending from Rivers and passes through Bayelsa, Akwa Ibom, Cross Rivers State, Delta, Ondo, Ogun and Lagos States, all of which share their southern border with the Atlantic Ocean and has been reported in several literatures. [Adeyemo et al, 2017[16]; Ohwoghere-Asuma, and Oghenevovwero 2017 [17]; Oloruntola et al, 2019[18]; Yusuf et al, 2021[19]; Atuluchukwu et al, 2022 [20]; A ah et al, 2018 [21]; Edet 2017 [22], Akerele et al, 2023[23], Inim et al, 2020 [24], Obunadike et al, 2024 [25]]. The works of Oteri and Atolagbe (2003) [26] reported that salt water incursion has been occurring especially in coastal areas of the Niger Delta, Nigeria.…”
Section: Introductionmentioning
confidence: 99%